Absinthin attenuates LPS-induced ALI through MIP-1α-mediated inflammatory cell infiltration. (21st October 2015) - Guo, Nailiang; Xu, Yinghua; Cao, Zhongqiang
ABSTRACT: Acute lung injury (ALI) is characterized by severe lung inflammation, and anti-inflammatory treatment is proposed to be a pertinent therapeutic strategy for the disease. Absinthin is a triterpene, extracted from a Chinese herb, with anti-inflammatory properties. The aim of this study was to evaluate whether absinthin can attenuate ALI in a mouse model of lung injury. Mice were treated with various concentrations (20 mg/kg, 40 mg/kg, and 80mg/kg) of absinthin, and lipopolysaccharide (LPS) to induce ALI. We found that the administration of absinthin relieved LPS-induced acute lung injury, as suggested by reduced histological scores, wet-to-dry ratio, myeloperoxidase activity, and accumulation of inflammatory cells in lung bronchoalveolar lavage fluid. Moreover, we demonstrated that absinthin significantly enhanced the expression of matrix metalloproteinase-8 (MMP-8); this effect could inhibit the accumulation of inflammatory cells in lung tissues through a mechanism dependent on MMP-8-mediated inactivation of macrophage inflammatory protein-1α. Therefore, we propose that absinthin is a promising novel therapeutic candidate for the treatment of ALI.